Resposta da comunidade de formigas (Hymenoptera: Formicidae) a atributos da vegetação em fragmentos florestais na Amazônia Oriental Brasileira - SILVA, Joudellys Andrade (2016)
In the Amazon, most forest remnants are fragmented and have a high degree of deforestation. The state of Maranhão is no exception to this rule and the fact that there are no systematized studies in the state showing how these impacts may interfere with the ant community makes this scenario even more worrying. However, canopy opening and litter depth, because they are more closely related to soil surface characteristics, seem to have greater influence on the epigeal ant community. To test this hypothesis, we try to evaluate which vegetation characteristics determine the richness and composition of ants. In order to do this, we installed six transects of 150m with six sample points each, 30m apart from each other, in each of the six sampled fragments. At each sampling point, a pitfall and a pair of baits (sweet and salty) were installed, totaling 36 pitfalls and 36 pairs of baits in each fragment. For vegetation, we measured litter height, canopy opening, circumference at chest height, height, distance and density of trees. We found 85 species of ants, and in the pitfall scale, canopy cover was the most important factor explaining the richness and composition of the ant species in all the sites sampled, while in the scale of transects, circumference and the density of trees Explained the composition of the sampled assembly. Our results suggest that microhabitats provided by the canopy determine the richness of the ants community, while other characteristics of the vegetation are influenced more strongly by the composition of species in larger scales.